(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize evidence on the association between digital addiction and mental health among Vietnamese adolescents and young people. Methods: This systematic review was conducted in accordance with the PRISMA guidelines. Articles were searched in PubMed and Google Scholar from 2016 to 2026 using keywords related to digital addiction and mental health. Cross-sectional studies conducted among Vietnamese adolescent and youth populations were selected based on predefined eligibility criteria. Study quality was assessed using the Joanna Briggs Institute (JBI) critical appraisal tools. Results: A total of 11 studies involving 12,931 participants were included in the analysis. Forms of digital addiction included internet addiction, smartphone addiction, and social media addiction. The prevalence of digital addiction ranged from 7.3% to over 69.2%, depending on the study population. The findings showed that digital addiction was significantly associated with mental health problems. Specifically, 8 of 11 studies reported an association with depression, 6 of 11 with anxiety, and 5 of 11 with other psychological problems such as stress, loneliness, sleep disturbances, and reduced quality of life. Conclusion: Digital addiction is significantly associated with mental health problems among adolescents and young people in Vietnam, highlighting the need for appropriate intervention and prevention strategies.